Hubungan Kecemasan Ibu Hamil dengan Covid 19 di Wilayah Kerja Puskesmas Parongpong - Nidya Ikha Putri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Covid 19 is a very global issue that is volatile so that it paralyzes community activities and services, especially in the field of health worldwide.. Safe or not in pregnancy examination during the pandemic. Unpreparedness of mothers facing childbirth is one of the contributing factors to the high maternal mortality rate (AKI) and infant mortality rate (AKB). The occurrence of maternal death is related to direct causal factors and indirect causes. This research is an analytical survey with Cross Sectional design. The population in this study is pregnant women who live in the working area of in primary Health Center at Parongpong . The samples in this study are some pregnant women trimester III who live in the Working Area of in primary Health Center at Parongpong and sampling by Cluster Random Sampling method. So the large sample in this study was 40 People. The results of the study obtained the frequency of respondents more respondents are quite readiness to Based on the results of the Significant value of p <0.05, it is said that the variable has no relationship between anxiety and exposure to Covid 19 pandemic in Primary Health Center at Parongpong The anxiety factor for pregnant women is related to the Covid-19 pandemic, not only being exposed to Covid-19, but also how the delivery process for the mother will be and whether the baby to be born will be healthy and not exposed to Covid-19 in working area of in primary Health Center at Parongpong. It is hoped that counseling activities will be increased regarding the importance of readiness facing childbirth and not worrying so that people are facing childbirth during the Covid 19 pandemic